PENGARUH PROFITABILITAS, KECUKUPAN MODAL DAN LIKUIDITAS TERHADAP MANAJEMEN LABA PADA E NTITAS PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Mulyaningtyas; Eka Fitri Handayani (Jurusan Akuntansi,Fakultas Bisnis dan Ekonomika,Universitas Surabaya, 2022)
This aim of this study is to find out: (1) the influence of profitability on earning management (2) the influence of capital adequacy on earnings management (3) the influence of liquidity on earning management. The population taken in this study are banking entities registered in the period 2016-2018 in the IDX as many as 43 entities, sample selection using purposive sampling techniques and obtained by 28 bank entities. Multiple regression analysis techniques became a hypothesis test tool in this study. The results of this study show that: (1) profitability does not affect earning management (2) Capital adequacy affects earning management (3) liquidity does not affect earning management.